Analisis Ikonisitas Visual karakter Utama Pada Film The Watchmen - Saptodewo, Febrianto; Qeis, Muhammad Iqbal; Sidhartani, Santi; Anto, Puji (Universitas Multimedia Nusantara, 2024)
Film has become a powerful medium for introducing complex and deep characters to its audience. This research adopts an approach in the field of visual communication design to explore how the main characters in the film